Tiny house/single-family house construction using ferrocement wall panels. Issue 12 (19th December 2021) - Saleem, Muhammad Azhar; Saleem, Muhammad Mazhar; Irfan-ul-Hassan, Muhammad
Abstract : The tiny house concept originated in the USA in the 1990s and gained momentum during the economic recession. The idea is to 'live-small' to save natural resources: be sustainable, environmentally friendly and energy efficient. Young professionals and new couples prefer to live-small to meet the economic challenges arising at the early stage of their careers. Therefore, research is needed to devise low-cost construction techniques and develop cheap materials in order to make inexpensive housing available to common people. The main objective of this study was to perform proof testing of full-scale ferrocement wall panels for use in a tiny house or a typical single-family house. Eighteen ferrocement panels reinforced with galvanised iron mesh were tested in compression and flexure. The results of testing demonstrate that ferrocement panels are capable of withstanding the expected wind and gravity loading. Their high ductility and energy absorption make them favourable for areas prone to seismic activity. Evaluation of man hours shows that a ferrocement panel house can be ready for living in less than one/fifth of the time as compared to its brick counterpart.